Analysis of refrigeration equipment in school nutrition programs in the USDA/FNS Southwest Region - Webb, Virginia Susan (Kansas State University, 2012)
Equipment to store foods at proper temperatures is critical to serving safe and nutritious meals in schools yet little is known about the amount or the adequacy of refrigerated storage in school nutrition programs. The purposes of this study were to identify the types and capacity of refrigeration equipment used in schools, determine the perceived adequacy of refrigerated storage capacity to meet new meal pattern requirements, and examine differences in adequacy and capacity. A modified Delphi technique, site observations, pilot study, and electronic survey were used for data collection. School nutrition directors in the USDA/FNS Southwest Region (N=2392) served as the population. Respondents provided an inventory of refrigeration equipment for one of the schools in their district and information about perceived adequacy of refrigerated storage, barriers to purchasing refrigeration equipment, resources used to develop specifications, and practices to compensate for inadequate refrigerated storage in their program. Data analysis included descriptive statistics, independent sample t-tests, regression, and ANOVA. Over a third of directors indicated that refrigerated equipment was inadequate to meet new meal pattern requirements. Directors with more experience rated adequacy higher than directors with less experience. Milk coolers (n=212, 88.3%) and walk-in freezers (n=180, 75.0%) were the types of refrigeration equipment found most often in schools. Walk-in freezers and refrigerators provided over 95% of refrigerated storage space. The mean average cubic feet of refrigerated storage per school was 1423±1152. School enrollment is a significant predictor of refrigerated storage capacity. Refrigerated storage is a concern for school nutrition directors who reported practices to compensate for inadequate storage including maintaining low inventory and decreasing the number of items purchased. School nutrition professionals may use the results of this study to implement practices to compensate for inadequate refrigerated storage. Results cannot be generalized due to the regional nature of the survey and low response rate and possible non-response bias.
Keywords: Refrigeration equipment; School nutrition; Adequacy of refrigeration; Refrigeration capacity; Management (0454); Nutrition (0570)